The Digital Paradox: Cyber Harassment of Women in Pakistan under Workplace Harassment Act 2010 and Prevention of Electronic Crime Act 2016 - Malik Amir Shahzad; Abubakar Nauman ul Haq; Muhammad Irfan Arbi (International Journal for Electronic Crime Investigation, 2024)
In preview of the Constitution of Islamic Republic of Pakistan. The Protection against Harassment of Women at the Workplace Act 2010 is a delayed legislation to ensure the provision of a secured workplace for women in Pakistan while, our country is responsible to respond the international requirements of ILO and CEDAW conventions in respect of women protection and women empowerment. Unfortunately, the implementation of this Act remained in question in public as well as in the private sector since its promulgation. On other hand, the revolution in digital communication has entirely changed the dynamics of professional environment globally. In Pakistan issue of cyber harassment at workplace is addressed by two key laws i.e., Workplace Harassment Act 2010 and Prevention of Electronic Crime Act 2016.This study firstly, condenses the factors due to which harassment law remained failed to serve its purpose in letter and spirit. Secondly, this insight provides critical analysis of effectiveness and interplay of these laws in addressing the issues, including their overlapping yet distinct domains, recognizing potential skirmishes, enforcement challenges and gapes in implementations. Thirdly, it evaluates whether existing legislations are compatible enough to contest the evolving nature of workplace cyber harassment in a rapidly digitizing world. At the end, this paper concludes with recommendations to enhance legal coherence and improve workplace protections against cyber harassment in Pakistan, emphasizing need for robust enforcement strategies, alertness campaigns and policy transformations.